Enhancing Vocabulary through English Subtitles - Rulina, Nessa; Harefa, Yulianus; Syahputra, Fikry Prastya (Talenta Publisher, 2025)
This study aims to analyze whether the use of English subtitled movies in Frozen II can enrich and improve students' vocabulary. The researcher collected data through pre-test, treatment and post-test, to identify and classify the improvement in the movie Frozen II. This study used descriptive quantitative method. As a result, this study states that in the pre-test the average score obtained by students is only 66.7. Students who pass the KKM (minimum completeness criteria) is 12 out of 23 respondents which means that the percentage of success criteria obtained is only 52%. Then in the post-test the average score obtained by students was 86.9 with the percentage of success criteria obtained was 91%. It can be concluded that implementing English movie subtitles to enrich students' vocabulary is effective based on the research results.